The Sustainability Coefficient of Urban Open Space Illumination Compliance as a Subjective Indicator of Environmental Comfort - Melita Rozman Cafuta (Applied Sciences)
Smart lighting of public open spaces plays a crucial role in creating sustainable cities. Investing in optimal methods for improving the energy efficiency of urban lighting systems has become strategic for the economic, technological, and social development of cities. In addition to technical considerations such as energy efficiency and photometric measurements, lighting design should also take into account the subjective aspect of visual safety. However, measuring lighting efficiency in terms of human perception can be challenging because people’s perceptions vary and depend on the urban and architectural context. To address this issue, a sustainability coefficient of outdoor lighting ambiences (Sn) is presented to quantify the compliance of urban open spaces with sustainable lighting design. This coefficient combines two subjective factors: illumination likability and perceived illuminance intensity. The study uses the SEC methodology (suitable for everyone, environmentally accepted, cost-effective), which provides insight into the factors that influence the Sn value. The results showed significant correlations between psychological and aesthetic-functional factors and the Sn, while sociological factors had little influence. The validity of the Sn in a realistic environment can be confirmed. The main reasons for certain Sn levels were identified and possible solutions were proposed, ranging from changes in lighting intensity to architectural redesigns, to improve environmental comfort in urban environments. This study paves the way for a deeper understanding of the role of urban lighting in shaping environmental comfort and human behavior.